mHealth intervention "ImTeCHO" to improve delivery of maternal, neonatal, and child care services-A cluster-randomized trial in tribal areas of Gujarat, India. - Dhiren Modi; Nishith Dholakia; Ravi Gopalan; Sethuraman Venkatraman; Kapilkumar Dave; Shobha Shah; Gayatri Desai; Shamim A Qazi; Anju Sinha; Ravindra Mohan Pandey; Ankit Anand; Shrey Desai; et al. (PLoS Medicine)
Background The coverage of community-based maternal, neonatal, and child health (MNCH) services remains low, especially in hard-to-reach areas. We evaluated the effectiveness of a mobile-phone-and web-based application, Innovative Mobile-phone Technology for Community Health Operations (ImTeCHO), as a job aid to the government's Accredited Social Health Activists (ASHAs) and Primary Health Center (PHC) staff to improve coverage of MNCH services in rural tribal communities of Gujarat, India. Methods and findings This open cluster-randomized trial was conducted in 22 PHCs in six tribal blocks of Bharuch and Narmada districts in India. The ImTeCHO mobile-phone-and web-based application included various technology-based job aids to facilitate scheduling of home visits, screening for complications, counseling during home visits, and supportive supervision by PHC staff. Primary outcome indicators were a composite index calculated based on coverage of important MNCH services and coverage of at least two home visitations by ASHA within the first week of birth. Primary analysis was intention to treat (ITT). Generalized Estimating Equation (GEE) was used to account for clustering. Eleven PHCs each were randomly allocated to the intervention (280 ASHAs, population: 234,134) and control (281 ASHAs, population: 242,809) arms. The intervention was implemented from February, 2016 to January, 2017. At the end of the implementation, 6,493 mothers were surveyed. Most of the surveyed women were tribal (5,571, 85.8%), and reported having a government-issued certificate for living below poverty line (4,916, 75.7%). The coverage of at least two home visits within first week of birth was 32.4% in the intervention clusters compared to 22.9% in the control clusters (adjusted effect size 10.2 [95% CI: 6.4, 14.0], p < 0.001). Mean number of home visits within first week of birth was 1.11 and 0.80 for intervention and control clusters, respectively (adjusted effect size 0.34 [95% CI: 0.23, 0.45], p < 0.001). The composite coverage index was 43.0% in the intervention clusters compared to 38.5% (adjusted effect size 4.9 [95% CI: 0.2, 9.5], p = 0.03) in the control clusters. There were substantial improvements in coverage home visits by ASHAs during antenatal period (adjusted effect size 15.7 [95% CI: 11.0, 20.4], p < 0.001), postnatal period (adjusted effect size 6.4, [95% CI: 3.2, 9.6], p <0.001), early initiation of breastfeeding (adjusted effect size 7.8 [95% CI: 4.2, 11.4], p < 0.001), and exclusive breastfeeding (adjusted effect size 13.4 [95% CI: 8.9, 17.9], p < 0.001). Number of infant and neonatal deaths was similar in the two arms in the ITT analysis. The limitations of the study include potential risk of inaccuracies in reporting events that occurred during pregnancy by the mothers and the duration of intervention being 12 months, which might be considered short. Conclusions In this study, we found that use of ImTeCHO mobile- and web-based application as a job aid by government ASHAs and PHC staff improved coverage and quality of MNCH services in hard-to-reach areas. Supportive supervision, change management, and timely resolution of technology-related issues were critical implementation considerations to ensure adherence to the intervention. Trial registration Study was registered at the Clinical Trial Registry of India (www.ctri.nic.in). Trial number: CTRI/2015/06/005847. The trial was registered (prospective) on 3 June, 2015. First enrollment was done on 26 August, 2015.